Hållbarhetsutvärdering av byggnader : Case Ripan i Kiruna - Sandberg, Karin; Pousette, Anna; Norén, Joakim; Sandberg, Marcus; Olofsson, Thomas; Mukkavaara, Jani (Luleå tekniska universitet, Industriellt och hållbart byggande, 2018)
Sustainability includes several parameters, and these can be measured and valued in many different ways. This study focuses on balancing the various parts to achieve sustainability by minimizing energy for heating and energy to produce the materials used in the building as well as minimizing cost for material investment and cost for heating using optimization techniques. This is balanced together with the environmental impact. This report describes an initial study for sustainability optimization of a smaller building. The goal is to develop a comprehensive approach to provide a broader basis of decisions for new construction. The calculation included the building envelope (exterior walls, roof and floors), interior walls and stabilizing elements for different frames of wood (timber frame and CLT). The result from the Ripan Case shows that the timber frame design has the lowest embodied energy and operating energy, and lowest cost for investment and heating during the operating phase. The environmental impact of the timber frame design was also low. Hållbarhet innefattar flera parametrar och dessa kan mätas och värderas på många olika sätt. Att väga ihop de olika delarna för att uppnå hållbarhet genom att minimera förbrukad energi för uppvärmning och energi för att producera material till bygget samt investeringskostnader för material och kostnader för uppvärmning är fokus i denna rapport. Detta vägs samman med miljöpåverkan. En inledande studie för hållbarhetsoptimering av en mindre byggnad är genomförd med målet är att utveckla en övergripande metod för att ge bredare beslutsunderlag vid nybyggnad. Beräkningar av inbyggd energi, driftsenergi, investerings- och uppvärmningskostnader har genomförts för ett planerat hus på Camp Ripan i Kiruna. I beräkningen av byggnaden inkluderades klimatskärm (ytterväggar, stomstabiliserande element och grund) för två olika stommar av trä (träregelstomme och KL-trä). För miljöberäkningarna användes främst indata från EPDer och resultatet redovisas i form av klimatpåverkan, ...